2014
DOI: 10.1111/str.12100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic High‐temperature Testing of an Iridium Alloy in Compression at High‐strain Rates

Abstract: Iridium alloys have superior strength and ductility at elevated temperatures, making them useful as structural materials for certain high-temperature applications. However, experimental data on their high-strain -rate performance are needed for understanding high-speed impacts in severe environments. Kolsky bars (also called split Hopkinson bars) have been extensively employed for high-strain -rate characterization of materials at room temperature, but it has been challenging to adapt them for the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Concerning the dynamic regime, not a single study of the dynamic response of pure iridium has been found in the literature apart from a few publications on stress-strain properties under dynamic and impact loading of DOP-26 (an iridium alloy containing 0.3 % of W to aid fabrication and approximately 40 ppm of Th to improve grain boundary cohesion at high temperatures), mainly motivated by the use of this material as cladding for radioisotope thermo-electric generator [15][16]. More recent publications have been found in the literature on the dynamic testing of DOP-26 alloy in tension [17][18] and compression [19] at different temperatures. In [18], an approach similar to those here proposed was applied to investigate the mechanical behaviour of the iridium alloy DOP-26 between 10 3 s -1 and 3×10 3 s -1 at high temperature (between 750 °C and 1030 °C).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Concerning the dynamic regime, not a single study of the dynamic response of pure iridium has been found in the literature apart from a few publications on stress-strain properties under dynamic and impact loading of DOP-26 (an iridium alloy containing 0.3 % of W to aid fabrication and approximately 40 ppm of Th to improve grain boundary cohesion at high temperatures), mainly motivated by the use of this material as cladding for radioisotope thermo-electric generator [15][16]. More recent publications have been found in the literature on the dynamic testing of DOP-26 alloy in tension [17][18] and compression [19] at different temperatures. In [18], an approach similar to those here proposed was applied to investigate the mechanical behaviour of the iridium alloy DOP-26 between 10 3 s -1 and 3×10 3 s -1 at high temperature (between 750 °C and 1030 °C).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It may result in a significant error in the strain measurements of the specimen, particularly when specimen strain is small. In order to limit the punching effect, high stiffness and high strength platens are placed between the bars and the specimen [5]. However, the introduction of the platens may cause wave disturbances resulting from a wave impedance mismatch and imperfections of the contact surfaces (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The split Hopkinson bar was largely applied to evaluate the strain rate sensitivity of materials at high strain rates; that is,̇∼< 5000 s −1 [1][2][3]. At very high strain rates (̇>∼ 5000 s −1 ), the direct-impact Hopkinson bar is now increasingly used [4,5].…”
Section: Introductionmentioning
confidence: 99%